Anti-tubercular activity of Callistemon citrinus and Piptadenistrum africanum on resistant strains of Mycobacterium tuberculosis using Microplate alamar blue assay - Bunalema, Lydia; Tabuti, John; Sekagya, Yahaya; Ogwang, Sam; Waako, Paul (ScopeMed, 2015)
Tuberculosis (TB) is one of the leading causes of death among infectious diseases in the world. It is responsible for killing approximately 1.4 million people per year worldwide. This devastating situation has steadily worsened, exacerbated by the emergence of drug-resistance and Human Immunodeficiency Virus (HIV) co-infection. The objectives of the study were to determine the minimum inhibitory concentration (MIC) of selected plant species on three TB strains and to determine different phytochemicals contained in the plant species. Methods: Microplate Alamar Blue Assay (MABA) was used to determine the MIC of two commonly mentioned plant species, Piptadenistrum africanum and Callistemon citrinus on resistant variant strains of Mycobacterium tuberculosis. Qualitative tests were used to determine the phytochemicals in the plants. Results: The chloroform extract of Callistemon spp. had MICs of 0.048mg/ml, 0.158mg/ml and 0.19mg/ml on the pan sensitive, isoniazid resisistant and rifampicin resistant strains respectively. P. africanum had MICs of 0.395 mg/ml, 0.395 mg/ml and 0.78 mg/ml on the pan sensitive, rifampicin and isoniazid resistant strains respectively. Conclusion: These plant species appear to be active not only on the pan sensitive strains of TB but also on resistant strains and could be developed into drugs for the treatment of Multi drug resistant (MDR) TB.
Keywords: Drug resistant tuberculosis; Mycobacteria; Efficacy; Medicinal plants